2021
DOI: 10.3390/cancers13225663
|View full text |Cite
|
Sign up to set email alerts
|

miRGalaxy: Galaxy-Based Framework for Interactive Analysis of microRNA and isomiR Sequencing Data

Abstract: Tools for microRNA (miR) sequencing data analyses are broadly used in biomedical research. However, the complexity of computational approaches still remains a challenge for biologists with scarce experience in data analytics and bioinformatics. Here, we present miRGalaxy, a Galaxy-based framework for comprehensive analysis of miRs and their sequence variants—miR isoforms (isomiRs). Though isomiRs are commonly reported in deep-sequencing experiments, their detailed structure complexity and specific differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The miRNA datasets were pre-processed and analyzed to identify the differentially expressed genes between healthy and infected MECs using Galaxy and R software [42]. The data was quality controlled using FastQC tool [43,44], and reads with average Phred quality less than 20 were removed.…”
Section: Data Collectionmentioning
confidence: 99%
“…The miRNA datasets were pre-processed and analyzed to identify the differentially expressed genes between healthy and infected MECs using Galaxy and R software [42]. The data was quality controlled using FastQC tool [43,44], and reads with average Phred quality less than 20 were removed.…”
Section: Data Collectionmentioning
confidence: 99%
“…In a different study, Diest and colleagues examined the value of nipple aspirate fluid as a source of valuable cancer biomolecules (such as microRNAs) for use in breast cancer liquid biopsy [ 8 ]. Additionally, Glogovitis et al demonstrated the application of a framework that is based on Galaxy [ 9 ]. miRGalaxy is an open-source platform for analyzing NGS data, focusing on microRNAs and their sequence variants—isomiRs (template and non-template)—across samples.…”
mentioning
confidence: 99%